Influence of the Casein Composite Genotype on Milk Quality and Coagulation Properties in the Endangered Agerolese Cattle Breed - Sara Albarella (Animals, 2020)
The aim of this study was the characterization of CSN1S1, CSN2 and CSN3 genetic variability in Agerolese cattle, and the investigation of the effect of casein composite genotypes (CSN1S1, CSN2 and CSN3) on quality and coagulation traits of the corresponding milk. To these purposes, blood and milk from 84 cows were sampled and analysed. Allele frequencies at CSN2 and CSN3 revealed no Hardy–Weinberg equilibrium in the population with a prevalence of allele A2 for CSN2 and allele B for CSN3. BBA1A2AB and BBA2A2AB composite genotypes were the most common in the population. BBA1A2AB showed a higher total solids and fat content (12.70 ± 0.16 and 3.93 ± 0.10, respectively), while BBA2A2BB showed the best coagulation properties (RCT 12.62 ± 0.81; k20 5.84 ± 0.37; a30 23.72 ± 1.10). Interestingly, the A2 allele of CSN2 was very widespread in the population; thus, it will be intriguing to verify if A2A2 Agerolese cattle milk and the derived cheese may have better nutraceutical characteristics.